Pengembangan Media Buku Interaktif Bergambar Pada Materi Perbandingan Jumlah Untuk Anak Usia Dini - Indriyani, Riski; Setyadi, Danang (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This research focuses on developing an interactive picture book as a learning medium to teach the concept of quantity comparison to early childhood learners. The study addresses a critical need for more effective and engaging educational tools, as conventional teaching methods often prove insufficient and are not well-suited to the cognitive characteristics of children in the preoperational stage. The research followed a Research and Development (R&D) approach, utilizing the ADDIE development model. This process encompasses the stages of analysis, design, development, implementation, and evaluation. A limited trial was conducted with 11 students from a kindergarten, aged 5-6 years. The findings from expert validation demonstrated that the medium is highly valid, achieving an average validity score of 96.36%. Additionally, practicality assessments provided very positive feedback, with a 90.9% score from teachers and a 91.24% score from parents, confirming the medium’s practical utility. The student trial also revealed a notable improvement in children's enthusiasm, active engagement, and overall comprehension of quantity comparison. Ultimately, this study's practical contribution is the development of a valid, practical, and effective innovative learning medium that can serve as a valuable resource for educators and parents.